Variasi Bahasa Dalam Film “Yowis Ben: Finale” Karya Bayu Skak (Kajian Sosiolinguistik) - Niko Dharmawan; Udjang Pairin Basir (STIKes Ibnu Sina Ajibarang, 2024)
In social life, language is very much needed as a means of social communication between one human being and another. The language used in society has a variety of languages, such as the language used in the film